2008
DOI: 10.3181/0710-rm-282
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic Conditioning Suppresses Nitric Oxide Production upon Myocardial Reperfusion

Abstract: Physiologically modulated concentrations of nitric oxide (NO) are generally beneficial, but excessive NO can injure myocardium by producing cytotoxic peroxynitrite. Recently we reported that intermittent, normobaric hypoxia conditioning (IHC) produced robust cardioprotection against infarction and lethal arrhythmias in a canine model of coronary occlusion-reperfusion. This study tested the hypothesis that IHC suppresses myocardial nitric oxide synthase (NOS) activity and thereby dampens explosive, excessive NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…This suggests that eNOS plays an important role in NO-induced acute hypotension (52). Furthermore, as was recently published by Ryou et al (57), a decrease in myocardial eNOS content by 30% was associated with a 60% reduction of enzyme activity and suppressed NO formation upon reperfusion of coronary arteries. Thus, it is plausible that reducing the increase of eNOS expression after ECE inhibition, as observed in our study, may be associated with a decrease of excessive NO generation during the development of myocardial ischemia in an employed model of coronary microembolization.…”
Section: Discussionsupporting
confidence: 56%
“…This suggests that eNOS plays an important role in NO-induced acute hypotension (52). Furthermore, as was recently published by Ryou et al (57), a decrease in myocardial eNOS content by 30% was associated with a 60% reduction of enzyme activity and suppressed NO formation upon reperfusion of coronary arteries. Thus, it is plausible that reducing the increase of eNOS expression after ECE inhibition, as observed in our study, may be associated with a decrease of excessive NO generation during the development of myocardial ischemia in an employed model of coronary microembolization.…”
Section: Discussionsupporting
confidence: 56%
“…Since typical IHT protocols expose subjects to moderate hypoxia intermittently for less than 2 h/day over at most three weeks, the stimulus for pulmonary hypertension and right ventricular hypertrophy should be minimal. In addition, IHT stimulates vasodilatory NO production, [111][112][113] which should delay the pulmonary hypertensive effects of hypoxia. Thus, it was not surprising that rats treated for 21 consecutive days with IHT had no right ventricular hypertrophy.…”
Section: Intermittent Hypoxic Training (Iht) Improves Cerebrovascularmentioning
confidence: 99%
“…In previous canine studies, we found that the same 20-day IHC program reduced myocardial NO production during IR. 62 Whether the IHC-induced reduction in the endothelial dysfunction observed in the current study resulted from reduced NO overproduction and oxidative stress remains to be determined.…”
Section: Discussionmentioning
confidence: 91%
“…Myocardial IR may cause acute NO overproduction and oxidative stress, 58,62 which would damage both myocardium and the coronary vasculature. 63 Recently, we reported that myocardial infarction caused endothelial dysfunction in rat aorta, 64 and Zhao et al showed that myocardial IR produced endothelial dysfunction in mesentery vessels.…”
Section: Discussionmentioning
confidence: 99%